Socioeconomic and Public Health Impacts of Waste Management in Piyungan Landfill, Bantul-Indonesia - Astuti, Farida Afriani; Syafrudin, Syafrudin; Susilowati, Indah (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
Piyungan Landfill in Bantul, Indonesia, still uses an open dumping system, leaving environmental impacts. This research examined the effects of open dumping on the socioeconomic and health conditions of nearby populations. Surveys and interviews using questionnaires were employed with households as the analysis unit. From four sub-villages (Ngablak, Banyakan III, Sentulrejo, and Baruwan I), 128 respondents were sampled randomly. Statistical quantitative analysis was employed to analyze the research data. Descriptive statistics were selected to describe sample data. Data were then expressed as percentages and presented in pie charts. Results show that for people who salvaged recyclables, the landfill was their primary source of livelihood. More than half (62.5%) earned an average of IDR1,093,095 (approximately USD70) per month as waste pickers. However, open dumping lowered the environment’s aesthetic value due to the unpleasant view and smell, and large populations of animals like rats, flies, cats, and mosquitoes attracted to waste piles. Nearly all respondents (90.6%) expressed their anxiety about these adverse effects, triggering social conflicts. It was claimed that property values and public health were, however, unaffected. Most respondents stated that the landfill did not lower the property values (96.9%) and did not cause health concerns (71.9%).